ANALISIS SIMULASI KEBIJAKAN UNTUK MENINGKATKAN PRODUKSI KEDELAI NASIONAL - Rizma Aldillah; Harianto Harianto; Heny Kuswanti Suwarsinah Daryanto (Jurnal Agribisnis Indonesia, 2014)
Soybean is the main strategic food commodities after paddy and maize, as stated in the UU No. 7 Tahun 1996. Since 2009 until now, national soybean consumption has reach about 2 illion tones per year, but national soybean production just able to satisfy around 900 thousand tones per year, so it drawbacks met from imported soybeans. Contribution quantity of soybean imports reached more 70 persen of the domestic soybean demand per year, this is opposite to the Government aim has launched several years ago to become self-sufficient in soybeans at 2014. So that, we need a policy government to support soybeans self-sufficiency program. Soybeans self-sufficient will be achieved when the national soybeans production can meet the domestic soybeans demand, so that, the policy needs to be done is how to increase the quantity of the national soybeans production. In this study, a simulation analysis was conducted to provide the some alternative policy to improve soybeans production. The results of the analysis concluded that the national soybeans production will increase, at least 15 percent per year by increasing 25 percent the quantity of soybean seeds, 15 percent area harvested, 20 percent of imported soybean prices, 25 percent of national soybeans price, 30 percent soybean import tariffs, and the last is decreasing 150 percent of the quantity soybean imports. Simulation is determined based on the average growth rate of the historical data used.